The Association between Personality Traits and OSCE-related Test Anxiety among Medical Science Students - Mirhosseini, Seyedmohammad; Ghasempour , Saeed; Bazghaleh, Milad; Abbasi , Ali; Basirinezhad, Mohammad Hasan; Rezvani, Fatemeh; Gholami, Tahereh; Ebrahimi, Hossein (Shahroud Journal of Medical Sciences, 2023)
Background Personality traits are effective factors in controlling feelings and emotions, including psychological distress. The present study was conducted with the aim of determining the relationship between personality traits and test anxiety in medical students under the Objective Structured Clinical Examination (OSCE). Methods This cross-sectional study was conducted with the participation of 176 medical science students by census sampling method in Iran. The inclusion criteria included studying in the first semester, having no history of addiction and suffering from psychological disorders, and the exclusion criterion was a previous history of participating in OSCE. Data collection tools included the demographic profile form, Sarason test anxiety questionnaires, and the short version of the Neo Personality Inventory (NEO-PI). Data were collected by self-report and analyzed using descriptive and inferential statistics. Results According to the results of the present study, most of the participants (64.8%) were female and (87.5%) were single. Out of all participants, about half of them (45.5%) reported moderate test anxiety. As among the five dominant personality profiles; Conscientiousness (40.9%) and neuroticism (8%) had the highest and lowest frequency, respectively. In addition, a significant relationship between personality traits and OSCE-related test anxiety was observed (p = .03). Conclusion The findings of the present study indicated that a significant number of students face OSCE-related test anxiety, which is related to their personality traits (conscientiousness and agreeableness). It is recommended to carry out psychological interventions according to each of the mentioned personality types in order to reduce the anxiety related to OSCE.